The Role of Ease of Digital Transactions in Increasing Customer Satisfaction at Pegadaian - Faizah, Naila (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Pegadaian has a very vital role in meeting the financial needs of the diverse and broad community as one of the important financial institutions. The purpose of this study is to analyze the role of ease of digital transactions in increasing customer satisfaction at Pegadaian. The research method used is qualitative with a descriptive approach. The research sample used was 2 people with data collection methods, namely interviews and observations. This research was conducted at Pegadaian Sidoarjo Regency, located on Jl. Raya Ngelom, in Taman District. The results of this study show that this digital transaction not only simplifies the transaction process, but also provides convenience in accessing Pegadaian services more efficiently. Overall, the use of digital transactions makes the customer experience with Pegadaian more practical and affordable.